1996
DOI: 10.1161/01.str.27.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Muscle Activity Before and After Botulinum Toxin Therapy for Lower Limb Extensor Spasticity in Chronic Hemiparetic Patients

Abstract: This study further supports the beneficial effects of botulinum toxin in the treatment of lower limb extensor spasticity. A correlation was observed between the clinical reduction of muscle tone, functional gait parameters, and a more normal EMG pattern with a predominant reduction of the premature activity of the plantar flexors. The qualitative type of EMG pattern corresponding to an increased stretch-reflex excitability (type I) was a positive predictor for the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 12 publications
3
69
0
13
Order By: Relevance
“…Over the last few years, it has been used to treat spasticity in upper and lower limbs in both adults and children [7, 8, 9, 10, 11, 12, 13, 14]. Although these studies have demonstrated a significant improvement in muscle tone, functional benefit has been less consistently demonstrated [15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, it has been used to treat spasticity in upper and lower limbs in both adults and children [7, 8, 9, 10, 11, 12, 13, 14]. Although these studies have demonstrated a significant improvement in muscle tone, functional benefit has been less consistently demonstrated [15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was recommended for the reduction of tone by the 2008 American Academy of Neurology (AAN) Practice Parameter [46]. An established procedure for drop foot is to inject into the gastrocnemius/soleus and/or tibialis posterior [11,46,[53][54][55][56][57][58][59]. This has been proposed as helpful in preventing "pistoning" out of the brace, improving forward tibial progression in stance, preventing skin breakdown, and reducing pain.…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…Hesse and colleagues examined 12 subjects with chronic spastic hemiplegia from stroke [56]. All subjects were injected with BTA (onabotulinumtoxinA).…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…Subsequently, Hesse et al 55 injected 400 U of BTX (Botox) to the spastic calf muscles of 12 patients and has been able to show statistically significant improvement in gait analysis parameters, including velocity, stride length and stance symmetry. In another study with a similar number of patients and injected muscles, Hesse et al 56 have investigated the effect of BTX on ankle muscle activity using dynamic electromyography. While correlation has been observed between muscle tone reduction and gait parameters, significant improvements have also been reported for walking speed, stride length and premature activity of soleus muscle after injection.…”
Section: Btx For Lower Limb Spasticitymentioning
confidence: 99%